2004
DOI: 10.1086/380226
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Identification of DENIS-selected Brown Dwarf Candidates in the Upper Scorpius OB Association

Abstract: We present low-resolution (R=900) optical (576.1-1,051.1 nm) spectroscopic observations of 40 candidate very low-mass members in the Upper Scorpius OB association. These objects were selected using the I, J and K photometry available in the DENIS database. We have derived spectral types and we have measured Hα and NaI doublet (at 818.3 and 819.5 nm) equivalent widths. We assess the youth of the objects by comparing them to their older counterparts of similar spectral type in the Pleiades cluster and the field.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
180
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(192 citation statements)
references
References 36 publications
12
180
0
Order By: Relevance
“…3, all of the 7 targets in the Upper Sco OB association (solid hexagons) have weak NaI as expected for young brown dwarfs. Putting this result together with the 28 very low-mass objects confirmed by Martín et al 2004, brings the total number of DENIS discovered Upper Sco members to 35. Two of our candidates have relatively early M type and no detectable NaI doublet.…”
Section: Nm) Doublet Detectable But Weaker Than Field Counterparts Obmentioning
confidence: 95%
See 1 more Smart Citation
“…3, all of the 7 targets in the Upper Sco OB association (solid hexagons) have weak NaI as expected for young brown dwarfs. Putting this result together with the 28 very low-mass objects confirmed by Martín et al 2004, brings the total number of DENIS discovered Upper Sco members to 35. Two of our candidates have relatively early M type and no detectable NaI doublet.…”
Section: Nm) Doublet Detectable But Weaker Than Field Counterparts Obmentioning
confidence: 95%
“…The PC3 index defined by the latter authors has been used in several papers to determine spectral types (Crifo et al 2005;Martín et al 2004Martín et al , 2006Phan-Bao & Bessell 2006Reylé et al 2006). Comparisons with other methods of spectral type determination have found that the results are consistent.…”
Section: Spectral Typesmentioning
confidence: 99%
“…Our sample consists of three groups of objects: firstly photometric USco candidates selected from the UKIDSS GCS Science Verification (Lodieu et al 2007b); secondly, a few known spectroscopic members falling in the instrument field-of-view and published in the literature (Martín et al 2004;Slesnick et al 2006), and, finally a sample of photometric non-members.…”
Section: The Samplesmentioning
confidence: 99%
“…The second sample consists of five known spectroscopic members with spectral types estimated from optical data with an accuracy of half a subclass: DENIS1610−2212 (Martín et al 2004), SCH1611−2217, SCH1612−2349, SCH1612−2338, and SCH1613−2305 (Slesnick et al 2006). These five objects fell in the AAOmega field-of-view and serve as spectral templates for assigning spectral types to our candidates.…”
Section: The Samplesmentioning
confidence: 99%
See 1 more Smart Citation